2022
DOI: 10.1155/2022/2984803
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bus Special Lane Performance Using Statistical Analysis and Optimization of the Signalized Intersection Delay by Machine Learning Methods

Abstract: Nowadays, the performance analysis and evaluation of public transportation systems have great importance in traffic engineering science. So far, the bus system has not been very effective in some cities in Iran, and many management approaches such as the allocation of special lanes and regular bus scheduling, which are needed to increase the efficiency of this system, have not been sufficiently considered. The purpose of the present study is to optimize the delay of the signalized intersection of bus lane and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…If the sig. amount (p value) is greater than the critical value (0.05) for a fixed significance level, the null hypothesis of normality rejects, indicating that the normality assumption of the desired distribution is rejected [24].…”
Section: Kolmogorov-smirnov (K-s) Testmentioning
confidence: 97%
“…If the sig. amount (p value) is greater than the critical value (0.05) for a fixed significance level, the null hypothesis of normality rejects, indicating that the normality assumption of the desired distribution is rejected [24].…”
Section: Kolmogorov-smirnov (K-s) Testmentioning
confidence: 97%
“…It was found that if the frequency of position/time data increases, the estimation method can be improved [13][14][15]. Research in the field of artificial intelligence systems is using artificial neural networks (ANN) as a framework in which to investigate many traffic and transportation problems [16,17]. One of the advantages of ANN is its use in model correlation and error correction to represent a problem [18].…”
Section: Introductionmentioning
confidence: 99%